2005
DOI: 10.1021/ja052452n
|View full text |Cite
|
Sign up to set email alerts
|

NMR Heteronuclear Correlation between Quadrupolar Nuclei in Solids

Abstract: We show for the first time that it is possible to acquire high-resolution heteronuclear NMR correlation experiments in solid state between second-order-broadened half integer quadrupolar nuclei (i.e., 27Al and 17O) using the scalar J-coupling. The sensitivity of the experiment is dramatically improved at high fields (gain proportional to the fourth power of the principal field) with a combination of signal enhancement techniques. This turns a challenging experiment into a real tool. We apply this experiment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 26 publications
8
150
1
2
Order By: Relevance
“…The fraction of OAl 3 triclusters formed by tetrahedral Al alone is 14.5% for 50CaO glass and 9% for 64CaO glass in our models. These values are slightly higher than the values reported by Drewitt et al (18) for the liquid, and the NMR results for the 50CaO glass (13).…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…The fraction of OAl 3 triclusters formed by tetrahedral Al alone is 14.5% for 50CaO glass and 9% for 64CaO glass in our models. These values are slightly higher than the values reported by Drewitt et al (18) for the liquid, and the NMR results for the 50CaO glass (13).…”
Section: Resultscontrasting
confidence: 63%
“…McMillan et al (12) performed 27 Al NMR measurements on CA glasses and found that Al 2 O 3 -poor composition glass has only fourfold coordinated Al atoms. Recent high-resolution NMR techniques (13) detected the formation of ∼5% OAl 3 triclusters (oxygen coordinating three Al atoms) in 50 mol % CaO-50 mol % Al 2 O 3 glass (50CaO glass), which are abundant in liquid Al 2 O 3 and may obstruct the vitrification process.…”
mentioning
confidence: 99%
“…Although connectivity of all three Al species to all three 31 P resonances was observed, the intensity of the crosspeaks show clear differences, reflecting the different magnitude of the J couplings. Recently, a modified J-HMQC experiment has been performed using the J coupling between two quadrupolar nuclei for the first time (178). This work used the J coupling between 27 Al and 17 O in crystalline CaAl 2 O 7 (grossite) with 30% 17 O enrichment and a glass, CaAl 2 O 4 , also with 30% 17 O enrichment.…”
Section: Concepts In Magnetic Resonancementioning
confidence: 99%
“…As a through space interaction it means it only provides information on spatial proximity and not bonding. Indirect detection of coupling via INEPT of J-HMQC has allowed various connectivities in inorganic systems to be determined [36]. Correlation techniques for quadrupolar nuclei have been recently reviewed in…”
Section: Correlation Experimentsmentioning
confidence: 99%